Decolonising the Museum Narrative: A Critical Analysis of Exhibition Texts in the Perak Museum and Borneo Cultures Museum (MINDEN Journal of History and Archaeology, 2026)
Museum decolonisation is a vital process for dismantling colonial legacies embedded within institutional narratives and representations. However, a significant research gap exists regarding the linguistic construction of exhibition texts as specific sites of decolonial practice within Malaysian museum studies. This study critically examines exhibition texts at the Perak Museum and the Borneo Cultures Museum (BCM). The methodology employs a theoretical framework integrating the concepts of ‘epistemic arrest’, linguistic decolonisation, and indigenous storytelling. Findings reveal that the Perak Museum retains an enduring colonial gaze, presenting local history as fragmented and ahistorical. While the BCM demonstrates progress in representing indigenous cosmologies, its historical narrative paradoxically reinforces colonial perspectives by sidelining Malay-Islamic history and using biased terminology that criminalises anti-colonial resistance. These results imply an urgent necessity to shift decolonisation efforts toward reformulating exhibition language. By addressing these linguistic frameworks, museums can move beyond ‘inherited memories’ to restore suppressed accounts of sovereignty and affirm indigenous civilisations.Keywords: museum decolonisation, colonial gaze, exhibition text, museums in Malaysia